The principle of non-interference in ASEAN: Revisiting an old and tested strategy in regional cooperation - Othman, Muhammad Fuad; Othman, Zaheruddin (Universitas Islam Riau Indonesia, 2010)
The Principle of Non-interference into the internal affairs of ASEAN member states has been the long and trusted ‘modus operandi’ since the inception of the Association in 1967. This method of non-inclusiveness relation has gone through several phases of changes in almost all fields of cooperation except when it concerns political-security issues. This paper intends to discuss why this principle has been accepted, embraced and defended by most of ASEAN members despite urges from international community to the association to modify the doctrine in order to make ASEAN relevant and progressive. The reoccurrence of the `Myanmar Issue’, the politically motivated court case against Aung Sun Suu Kyii, has once again marred ASEAN’s image as a regional power house. In the final analysis, the author wish to propose some significant amendments to the Treaty of Amity and Cooperation (TAC) which embedded the non-interference principle as one of the most important pre-requisite in intraregional relations.